Kesesuaian Layanan Informasi Publik Perangkat Daerah Pemerintah Provinsi Jawa Tengah Di Tahun 2017-2018 Melalui Situs Dengan Peraturan Komisi Informasi (PerKI) No. 1 Tahun 2010 - Andreas Pandiangan; Elva Visoladilla Indi (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2020)
This research is based on public information disclosure which is an individual right and is realized through the availability of information. The availability of such information should be open and transparent. The purpoce of this research is to khow the extent of the Central Java Provincial Government regional institution suitability which have been provided information services based on PerKI No. 1 (2010), through the sites during 2017. The qualitative approaches that used in this research are descriptive analysis techniques anf interative analysis of miles and Huberman. The subjects of this research were public information services at 32 Central Jawa Provincial OPD through the sites during 2017. On an whole view, The Central Java Provincial Government organizations have not fully complied the standards of procedures PerKI No. 1 (2010), in providing information services based on Perki No. 1 (2010) thru the sites during 2017. The result is show through data numeration based Daftar Informasi Publik (DIP) score anf available information on it’s site such as; organizational structure of PPID, PPID duties and DIP.